Deforming Spondylosis in a Burmese python (Python bivittatus) - Maria Sinara de Matos Silva; Jinarla Kelly da Silva Barros; Rita Ferreira Gonçalves da Silva; Maria Ruth Gonçalves da Penha; Tainá Marques Bertuzzi; Diego Pontes Soares; Thiago Ferreira Lopes Nery; Layze Cilmara Alves da Silva Vieira (Acta Scientiae Veterinariae, 2026)
Background: Deforming Spondylosis (DS) is a lesion often attributed to changes in the spine. It is a degenerative disease characterized by the presence of one or more osteophytes in the vertebral bodies at different degrees of development. When severe, it causes dorsal stiffness, lameness, gait alterations and pain. Domestic and wild animals can develop this disorder due to management failures, exposure to pathogens, or aging. This pathology may also appear adjacent to a degenerated, protruded, or normal intervertebral disc, associated with a site of spinal instability, but its etiology is often idiopathic. The diagnosis is confirmed by characteristic radiographic findings, such as loss of definition of vertebral endplate margins, narrowing or collapse of the intervertebral disc space, varying degrees and/or combinations of endplate lysis, sclerosis, and bone proliferation. This paper describes the 1st report in Brazil of a case of Spondylosis Deformans in a Burmese python, an exotic snake. Case: An approximately 16-year-old male adult Burmese python (Python bivittatus), kept in captivity at the Arruda Câmara Zoobotanical Park (BICA) in João Pessoa, Paraíba state, showed episodes of apathy and lethargy within the enclosure. The serpent is from abandonment, suspected of being a trafficking animal due to the absence of a microchip and a history of irregular delivery. For diagnostic support, the following procedures were performed in addition to physical, radiographic, cytopathological, and histopathological examinations. The cytopathological analysis revealed a hypocellular content immersed in a background containing red blood cells and thrombocytes. The content was characterized by heterophiles, monocytes, osteoblasts, occasional lymphocytes and mast cells, as well as rare eosinophils, being compatible with an active chronic inflammatory process. No infectious and/or parasitic agents were evidenced. The radiographic examination revealed altered vertebral alignment, decreased intervertebral spaces, and bone tissue proliferation. Histopathological analysis of the lesion revealed proliferation of reactive bone tissue, characterized by immature bone trabeculae (osteoid). Based on the analysis of the requested tests associated with the animal's clinical condition, it was found that the snake had a case of deforming spondylosis. The animal was monitored, maintaining the management previously adopted by the veterinarians at the facility until the clinical condition stabilized. Discussion: The clinical, cytological, and radiographic study of the lesion allowed the visualization of physical and cellular alterations similar to those described in the literature, confirming a case of deforming spondylosis, one of several diseases that affect the spine. Although the pathology may be present in other snakes kept in captivity, its occurrence may be underdiagnosed due to the absence of routine radiographic examinations and a lack of knowledge of the clinical signs compatible with the disease. The hypothesis is raised that, in this animal, deforming spondylosis was related to factors of inadequate management before the snake's referral to the zoo. This report emphasizes the importance of clinical monitoring and continuous complementary examinations in captive snakes, allowing for the early diagnosis of osteoarticular diseases and the adoption of preventive measures that improve the quality of life of these animals. Keywords: serpent’s lesions, snake’s lesions, radiographic findings, osteometabolic problems.